The Palestinian human right to full Israeli citizenship: Between settler colonialism and a hard place - Samuel, M.T. (Frontiers in Political Science, 2022)
This article examines the utility of a legal analysis supporting the recognition of a Palestinian human right to Israeli citizenship in advancing equality in Israel-Palestine under the one-state reality. It does so by assessing the workings of Israeli citizenship in light of the theoretical frameworks of the nation-state and settler colonialism and demonstrates the importance of treating the two frameworks as complementary, rather than mutually exclusive, in analyses involving Palestinian rights. It argues that the struggle for Palestinian equality is not only a legal one but also a moral one, whose success depends on a nuanced understanding of the functioning of law in settler colonialism.